2016
DOI: 10.1103/physrevb.94.235144
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary-field-based trial wave functions in quantum Monte Carlo calculations

Abstract: Quantum Monte Carlo (QMC) algorithms have long relied on Jastrow factors to incorporate dynamic correlation into trial wave functions. While Jastrow-type wave functions have been widely employed in real-space algorithms, they have seen limited use in second-quantized QMC methods, particularly in projection methods that involve a stochastic evolution of the wave function in imaginary time. Here we propose a scheme for generating Jastrow-type correlated trial wave functions for auxiliary-field QMC methods. The m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Using the approach developed in Ref. 71, one can use Jastrow correlated wavefunctions in AFQMC as well.…”
Section: Discussionmentioning
confidence: 99%
“…Using the approach developed in Ref. 71, one can use Jastrow correlated wavefunctions in AFQMC as well.…”
Section: Discussionmentioning
confidence: 99%
“…can improve accuracy, reduce time-step error, local energy fluctuations and the imaginary time needed to reach equilibration of walker ensembles (Al-Saidi, Chang, Rubenstein, & Morales, 2016). Other form of trial wave functions have also been used, including generalized valence bond (GVB) in molecules (Purwanto et al, 2008) and numberprojected Bardeen-Cooper-Schrieffer (BCS) trial wave functions in atomic gases (Carlson, Gandolfi, Schmidt, & Zhang, 2011).…”
Section: The Phaseless Approximationmentioning
confidence: 99%
“…Often using a single SD, such as the HF or DFT wave function, delivers results of excellent accuracy. Use of multideterminant trial wave functions: ΨTfalse〉=d=1NdAdΨdfalse〉 can improve accuracy, reduce time‐step error, local energy fluctuations and the imaginary time needed to reach equilibration of walker ensembles (Al‐Saidi, Zhang, & Krakauer, ; Chang, Rubenstein, & Morales, ). Other form of trial wave functions have also been used, including generalized valence bond (GVB) in molecules (Purwanto et al, ) and number‐projected Bardeen–Cooper–Schrieffer (BCS) trial wave functions in atomic gases (Carlson, Gandolfi, Schmidt, & Zhang, ).…”
Section: Constrained Afqmc Calculationsmentioning
confidence: 99%
“…It is thus important to have size-consistent alternatives. In addition to the single-determinant trial wave function, which has been shown to be very accurate in a large variety of systems, interesting possibilities exist with GHF and symmetry-restoration 42 , BCS 43 and HFB 17 , and a stochastic representation of Jastrow factors 59 . Recently a selfconsistent constraint has been proposed and shown to further reduce the systematic error from the constrained path approximation in lattice model calculations, especially in quantities such as spin and charge density and the reduced density matrix 45,60 .…”
Section: Self-consistent Afqmcmentioning
confidence: 99%